PENERAPAN JURNALISME BERPERSPEKTIF GENDER DALAM BERITA PROSTITUSI ONLINE VANESSA ANGEL DI DETIK.COM - Rahmawati Latief; Faradhillah Azis (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2019)
This research aims to find out how to apply gender perspective journalism to the aspect of gender sensitivity, aspects of writing techniques, and aspects of the reportage technique in the news of the online prostitution of Vanessa Angel  in detik.com. The study used descriptive quantitative research with the approach of content analysis method. The results showed that the news of the online prostitution of Vanessa Angel in detik.com still did not fully apply gender perspective journalism  particularly in the category gender sensitivity or the alignments of women  until the women's coverage is still represented as a discriminatory object.